Special Section: Measuring the Value Added by Professional Technical Communicators - Carol Sanders Reiner (Journal of Applied Communications, 1995)
A summary of articles in a special section of the journal Technical Communication reporting on value added by technical communicators; the research and resulting articles are by Janice (Ginny) Redish and Judith A. Ramey.